If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-69x-13=87+39x
We move all terms to the left:
-69x-13-(87+39x)=0
We add all the numbers together, and all the variables
-69x-(39x+87)-13=0
We get rid of parentheses
-69x-39x-87-13=0
We add all the numbers together, and all the variables
-108x-100=0
We move all terms containing x to the left, all other terms to the right
-108x=100
x=100/-108
x=-25/27
| 16a-18a+-14a=-16 | | -123/40=9/10p+3/40 | | 3xx-5=2xx | | 7k-3k+3=31 | | -25=x-13 | | 100=1/2x | | -9=u/6-3 | | 16a−18a+-14a=-16 | | 9x-3(2x+4)=2(x-12) | | 7a–6=-1–11a | | 4(3x-9)=6(-6+2x) | | S35=x/16 | | 4x^2-16x+256=0 | | q=2.5P | | 2w+3=-15 | | 9m-15m=18 | | -92x+6=18-92x | | 90=x^2-x | | (4y×4y)+(5y+5y)=(19×19) | | 3(z-6)=9 | | x/5+6=6 | | 50x+23=23+50x | | -6+7(1-x)=-4(x-4) | | -3(-7x+32)=38(-39+6x) | | -9=-3+d | | 24y-9=14y+10 | | (4x×4x)+(5x+5x)=(19×19) | | Y=-x+-3+-2x+6 | | x4+2=4 | | 9x+45=6x+18 | | 5^(2x-7)=125 | | (3y+6)+(5y-10)+(2y+4)=180 |